1999
DOI: 10.1128/mcb.19.4.3010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the “Dispensable” Portions of RAG-1 and RAG-2 in V(D)J Recombination

Abstract: V(D)J recombination is initiated by introduction of site-specific double-stranded DNA breaks by the RAG-1 and RAG-2 proteins. The broken DNA ends are then joined by the cellular double-strand break repair machinery. Previous work has shown that truncated (core) versions of the RAG proteins can catalyze V(D)J recombination, although less efficiently than their full-length counterparts. It is not known whether truncating RAG-1 and/or RAG-2 affects the cleavage step or the joining step of recombination. Here we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 41 publications
(90 reference statements)
5
50
1
Order By: Relevance
“…This is supported by a recent study 29 showing that the removal of dispensable regions of RAG-1 and RAG-2 impairs proper processing of recombination substrates.…”
Section: Discussionsupporting
confidence: 74%
“…This is supported by a recent study 29 showing that the removal of dispensable regions of RAG-1 and RAG-2 impairs proper processing of recombination substrates.…”
Section: Discussionsupporting
confidence: 74%
“…We and others have observed that substitutions that disrupt the RING finger domain within the N-TR can virtually eliminate recombination despite the entire region's being dispensable for DNA cleavage (18 -20). It has also been demonstrated that cysteine-rich and arginine/lysinerich elements in the N-TR but outside the RING domain contribute to optimal levels of recombination activity (18,42), and that the N-TR as a whole promotes SJ formation (43). Taken together, these data strongly suggest that the N-TR plays a regulatory role.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, these three nucleotides have a clear in vivo function during stage 2 of V(D)J joining. It is possible that the interaction in question is fairly weak and/or transient, and it is of particular interest that nonamer-proximal nucleotides of the heptamer have been highlighted as a possible contact site for RAG1/2 in one modification interference study (43).…”
Section: Discussionmentioning
confidence: 99%